Perlindungan Hukum Bagi Pemilik Saham Dalam Proses Konversi Saham Warkat Ke Saham Tanpa Warkat (Scripless) di Indonesia (Studi Putusan Mahkamah Agung No. 1562 K/PID/2013) - Dara Aulia Yuman; Arta Nanda Kamila; Kayana Deeva Canthiqa (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The transition from certificated shares to scripless trading in Indonesia's securities market has introduced new legal vulnerabilities in the conversion process. This study analyzes the legal framework of share conversion and the forms of legal protection available to shareholders based on Supreme Court Decision Number 1562 K/PID/2013. Using a normative juridical method, the findings reveal that the primary legal risk lies in the transitional phase, particularly involving bearer shares transferred through unmonitored third parties. Legal protection for shareholders is multidimensional, covering criminal liability under Article 372 of the Criminal Code, civil redress under Article 1365 of the Civil Code, and administrative enforcement through the OJK.